Pengaruh Model Pembelajaran Word square Terhadap Hasil Belajar IPAS Siswa Sekolah Dasar - Harmawati; Sinta Maria Dewi; Yulistina Nur DS; Tia Latifatu Sa'diah; Ani Rahmawati (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to determine the effect of word square learning model on IPAS learning outcomes of fifth grade elementary school students of Lemahduhur II State Elementary School. This research is a type of quantitative research with a pre-experimental research design with a one group pretest-posttest model. The population used in this study were all students at SD Negeri Lemahduhur II as many as 194 students. The sample taken consisted of 25 students. The technique of collecting research data with Purposive Sampling. Technical data analysis to test the hypothesis was carried out by calculating descriptive and inferential statistics. The data was obtained from the pretest posttest results.  The results of hypothesis testing, there is a significant difference between pretest and posttest. This is obtained by the sig value. (2-tailed) for the test is 0.000 <0.05 then H0 is rejected. So with this hypothesis test shows that there is a positive and significant influence between the word square learning models on the learning outcomes of IPAS elementary school students.